PENGARUH PENGAWASAN DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN BANGLI - Wiadnyana Putra, I Wayan; Idayanti, I Dewa Agung Ayu Eka (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The determinant of the success of a business lies in its human resources, improving the quality of human resources is based on increasing discipline which will have an impact on the ease of achieving business goals. Supervision and job satisfaction can have an influence on workers' sense of discipline. The Bangli Regency Transportation Service will be the place for the study, using census techniques, 89 employees were determined to be used as the reference group. The study material that has been collected will be processed using a multiple regression model, the results found show both individually and simultaneously a direct and real influence on increasing the workers' sense of discipline.